Diversifying STEM Collections: Where We are Now and Future Considerations - Kelly Giles; Alyssa Young (Issues in Science and Technology Librarianship)
In academic libraries there has been growing interest in developing better ways to diversify collections, but STEM collections are sometimes overlooked. To better understand current practices and challenges, a survey was distributed to librarians with STEM collection responsibilities in the summer of 2021. Results from the survey indicated that STEM librarians care about improving the diversity of their collections but struggle with a lack of time, knowledge, and other resources needed to do so effectively.